2016
DOI: 10.1039/c5ra21636b
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the uranium adsorption behavior of mesoporous SBA-15 silicas decorated with alkylphosphine oxide ligands

Abstract: Alkylphosphine oxide functionalized mesoporous silicas were prepared by co-condensation and further addition reaction with secondary n-propylphosphine oxide and are promising candidates for the preconcentration and adsorption of uranium from acidic aqueous solutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…3(a) shows that the adsorption capacity of Fe 3 O 4 @Cyanex-923 increases with the pH increase to reach its utmost value at pH ∼5 and then levels off. This behavior is similar to that reported for silica coated with alkylphosphine oxides, 32 as higher uranium( vi ) adsorption was attained at pH 5. At low pH values, the predominant uranium species is UO 2 2+ which competes with the abundant H + and H 3 O + ions for the binding sites on the Fe 3 O 4 @Cyanex-923 surface, 46 and consequently the adsorption is unfavorable at low pH.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…3(a) shows that the adsorption capacity of Fe 3 O 4 @Cyanex-923 increases with the pH increase to reach its utmost value at pH ∼5 and then levels off. This behavior is similar to that reported for silica coated with alkylphosphine oxides, 32 as higher uranium( vi ) adsorption was attained at pH 5. At low pH values, the predominant uranium species is UO 2 2+ which competes with the abundant H + and H 3 O + ions for the binding sites on the Fe 3 O 4 @Cyanex-923 surface, 46 and consequently the adsorption is unfavorable at low pH.…”
Section: Resultssupporting
confidence: 89%
“…29,30 In particular, trialkylphosphine oxides are cost-effective neutral extractant with demonstrated high extraction capacity and high stability in strong acidic media, which makes them are excellent ligands to functionalize various adsorbents for uranium capture. 31,32 Cyanex-923 is a promising phosphine oxide extractant which revealed high radiation stability, good hydrolysis resistance, poor water solubility, and non-corrosive nature; 33,34 thus, it could be a potential candidate to be impregnated onto the Fe 3 O 4 surface for the efficient uranium adsorption.…”
Section: Introductionmentioning
confidence: 99%
“…To date, a variety of sorbents have been developed for exaction of uranium from highly acidic and/or radioactive medium, such as synthetic resins, mesoporous silica and covalent organic framework . For example, Subramanian et al .…”
Section: Introductionmentioning
confidence: 99%
“…In fact, a recent marine testing of a polymer fiber sorbent after 56-day seawater exposure showed that a significant amount of Na + ions was retained in the sorbent. 32 Thus, it is of great importance to illuminate the impact of salt on the solvation of Ca 2 UO 2 (CO 3 ) 3 in seawater. The present work seeks to simulate Ca 2 UO 2 (CO 3 ) 3 in seawater via classical MD simulation, by including Na + and Cl − ions explicitly in our model.…”
Section: Introductionmentioning
confidence: 99%